395 Young Scholar Award Talk: Melatonin: A Promising Therapeutic for Compromised Pregnancies. (21st September 2022) - Contreras-Correa, Zully E; Messman, Riley D; Sanchez-Rodriguez, Hector; Burnett, Derris D; Lemley, Caleb O
Abstract: Poorly functioning placenta restricts oxygen and nutrient supply to the fetus resulting in fetal nutrient deficiency and intrauterine growth restriction. Intrauterine growth restriction dramatically increases neonatal mortality and those who survive are more prone to experience metabolic diseases such as cardiovascular diseases, hypertension, and type 2 diabetes in later life. Therefore, the placenta plays a critical role in the developmental origins of health and diseases. Currently, there is a vast effort evaluating the effects of compromised pregnancies such as maternal undernutrition, overnutrition, and heat stress on fetal development; however fewer studies have evaluated potential therapeutics to enhance placental efficiency and offspring performance. Melatonin, a hormone that modulates circadian rhythms, has shown to increase umbilical and uterine blood flow in pregnant dams. Moreover, a recent study observed that melatonin therapeutic effects during compromised pregnancies are seasonally dependent. Dietary melatonin supplementation to pregnant beef cattle increased uterine blood flow, rescued fetal weights, increased angiogenic factors in the placenta, and reduced vaginal temperatures in the summer, but not in the fall. The same study found that maternal nutrient restriction was more detrimental during the fall reducing uterine blood flow. Additionally, it was observed that dams that are nutrient restricted during the summer exerted a compensatory mechanism at the placentome level where they exhibited greater placentome vascularity and increased placental capillary size and angiogenic factors. Lastly, bovine placental circadian rhythms have been identified and interestingly, temporal increases in placental vascularity occur concomitantly with greater melatonin receptor 1A transcript abundance. In conclusion, these findings provide a better understanding of placental insufficiency and impaired fetal growth during maternal nutrient restriction, while temporal alterations in the placenta could lead to the development of proper guidelines for administration of placental blood flow therapeutics such as melatonin. Future studies should evaluate melatonin impacts on offspring organ development and potential for mitigating heat stress in livestock.